Tonnageskatt i Sverige - En studie gällande effekterna av tonnageskattens införande - Forsman, Carl; Seiberlich, Oliver (My University, 2017)
This paper is a case study regarding the structure of the Swedish tonnage-tax system and its potential effects regarding the number of vessels with Swedish flag, through analysing information gathered by interviews and literature studies the goal is to describe how the Swedish tonnage-tax system works and state the pros- and cons of using it. Tonnage-tax is an alternative taxation system that is offered to shipping companies, Sweden recently decided to implement their own tonnage-tax system which happened on 1 January 2017. The goal of implementing the system is to increase the number of vessels with Swedish flag, a number that has steadily decreased during the last 10-15 years. Tonnage-taxation offer shipping companies the alternative to calculate their earnings through an equation which is based on the vessels net tonnage, a coefficient based on the net tonnage interval, price base amount and how long the vessel has been under the possession of the shipping company during the taxation year. Under results the writers have established an example which illustrates the calculation of tonnage-tax, the process is then compared to conventional taxation. The authors conclude that the Swedish tonnage-tax system will be beneficial in regards of profit taxation when the actual profit is higher than the one calculated using the tonnage-tax system. The authors also conclude that the Swedish tonnage-tax system includes regulation that contradicts the purpose of improving the competitive situation for Swedish Shipping since the tonnage-tax systems of other nations do not include the same regulation. Furthermore, it is concluded that Swedish flag still comes with disadvantages that do not exist under other nations flags, the most impactful being the criteria regarding hiring personnel from low paying countries. This means that the implementation of the Swedish tonnage-tax system raises the probability of more vessels choosing Swedish flag, however there are regulations within the system and regulation regarding Swedish flag which indicates it is still being inferior to many other nations.
Keywords: Transportteknik och logistik; Transport; Transport Systems and Logistics; Transport